Association of Gestational Diabetes Mellitus Diagnosed using the IADPSG and the POGS 75 gram Oral Glucose Tolerance Test Cut-off Values with Adverse Perinatal Outcomes in the Philippine General Hospital - Urbanozo, Hannah; Tan, Iris Thiele Isip- (Journal of the ASEAN Federation of Endocrine Societies, 2014)
<center> </center><center> </center><center>*Visual Abstracts prepared by Dr. Roy Raoul Felipe</center> Objective. To determine the association of adverse perinatal outcomes among women with gestational diabetes mellitus (GDM) according to the International Association of Diabetes and Pregnancy Study Groups (IADPSG) and the Philippine Obstetrical and Gynecological Society (POGS) diagnostic cut-offs for 75 g oral glucose tolerance test (OGTT). Methodology. A review of deliveries from September to December 2013 at the charity services of the Philippine General Hospital (PGH) looking at 75 g OGTT results and perinatal outcomes was done. The association between GDM and perinatal outcomes were estimated and tested using logistic regression analysis. The diagnostic accuracy between the POGS and the IADPSG criteria was tested by comparing their areas under the curve (AUC). Results. A total of 236 deliveries were included. The GDM group had a significantly increased risk for primary Caesarean section (CS) (OR=1.79, 95% CI: 1.02-3.16, p=0.041) and infant admission to the Neonatal Intensive Care Unit (NICU) (OR=2.66, 95% CI: 1.3-5.44, p=0.007). Per category of glycemia, a 1-hour OGTT value >180 mg/dL was associated with an increased risk for primary CS (OR=1.968, 95% CI: 1.08-3.55); a fasting blood sugar (FBS) >92 mg/dL with increased risk for large for gestational age (LGA) infants (OR=20.97, 95% CI 2.27-192.97); and elevated FBS, 1-hour and 2-hour OGTT blood glucose values with increased risk for infant admission to the NICU (OR=2.18, OR=2.39, OR=2.34, respectively). There was no significant difference in outcomes between women diagnosed using the IADPSG and POGS criteria (n=104) and those diagnosed with the IADPSG criteria only (n=90). Conclusion. The currently used cut-off values in diagnosing GDM was associated with increased risk for primary CS and infant admission to NICU. No significant difference in outcomes was found between the group of women that included those diagnosed with the more stringent POGS criteria from the group that excluded them, implying adequacy of the IADPSG thresholds for local use.